2013
DOI: 10.1080/01621459.2013.783842
|View full text |Cite|
|
Sign up to set email alerts
|

Copula-Based Regression Estimation and Inference

Abstract: In this paper we investigate a new approach of estimating a regression function based on copulas.The main idea behind this approach is to write the regression function in terms of a copula and marginal distributions. Once the copula and the marginal distributions are estimated we use the plug-in method to construct the new estimator. Because various methods are available in the literature for estimating both a copula and a distribution, this idea provides a rich and flexible alternative to many existing regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 24 publications
2
60
0
Order By: Relevance
“…A common feature of all publications in this direction consists in additional structural or parametric assumptions regarding the unknown regression function, such as additivity (see Stone 1985), tree-based models (Hastie, Tibshirani, and Friedman 2001) or single index models (Ichimura 1993). In a recent article, Noh, El Ghouch, and Bouezmarni (2013) introduced a novel semiparametric estimate of the regression function in a nonparametric regression model with a high-dimensional predictor. Roughly speaking, these authors proposed to model the dependency structure between the response and the predictor by a parametric copula family to obtain estimates of the regression function which converge with a parametric rate.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…A common feature of all publications in this direction consists in additional structural or parametric assumptions regarding the unknown regression function, such as additivity (see Stone 1985), tree-based models (Hastie, Tibshirani, and Friedman 2001) or single index models (Ichimura 1993). In a recent article, Noh, El Ghouch, and Bouezmarni (2013) introduced a novel semiparametric estimate of the regression function in a nonparametric regression model with a high-dimensional predictor. Roughly speaking, these authors proposed to model the dependency structure between the response and the predictor by a parametric copula family to obtain estimates of the regression function which converge with a parametric rate.…”
Section: Introductionmentioning
confidence: 98%
“…, x d ) T and C is the copula. Noh, El Ghouch, and Bouezmarni (2013) showed that the mean regression function m(x 1 , . .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Gaussian copula regression model has been widely used and well studied in the classical low-dimensional setting [40,7,24,30]. For example, [24] developed a systematic framework to make inference and implement model validation for the Gaussian copula regression model.…”
Section: Introductionmentioning
confidence: 99%
“…For example, [24] developed a systematic framework to make inference and implement model validation for the Gaussian copula regression model. [30] proposed a plug-in approach for estimating a regression function based on copulas, and presented the asymptotic normality of the estimator. However, their model and analysis are restricted to the low-dimensional setting and not well adapted to the high-dimensional case.…”
Section: Introductionmentioning
confidence: 99%